A Study on the Number of Simple Elements in Peripatetic Philosophy and Suhrawardi's Illuminative Philosophy - Saeed Anvari; AmirHosseyn Shahgoli (حکمت سینوی, 2019)
The leading theory regarding the number of basic elements in classical natural sciences is formulated in the peripatetic school of philosophy, which assumes four basic elements to exist. They propose three possible explanations in support of this theory: First, reasoning based on the position of objects in nature and their natural inclinations, taking into view the qualities of being light or heavy. Second, reasoning by considering fundamental sensible qualities all objects share (hotness, coldness, wetness, dryness). Third, reasoning by dint of composition and analysis. Then, instances of the four classical elements (earth, water, air, and fire) were determined through an inductive method of reasoning. Abou Reihan al-Biruoni and Suhrawardi were critical of this theory and refused to accept fire as a basic element, calling it hot air. Hence, by modifying the criteria behind the classification of basic elements, Suhrawardi categorized them according to their visual qualities and, therefore, reduced the number of elements to three: opaque (Hajez), translucent (Moghtased) and subtle (Latif). In this paper, the arguments deployed by the philosophers of the peripatetic school and constitutive of Suhrawardi's criticism about the four elements was investigated and it was revealed that Suhrawardi's motive in this new method of categorization, in which fire was removed from among basic elements, was more metaphysical, and did not, in fact, abide by the rules of natural sciences.